Phenalenone Derivatives: The Voyage from Photosensitizers to Push-Pull Fluorescent Molecules - Silva-Molina, C; Silva-Molina, C; Sandoval-Altamirano, C (Elsevier B.V., 2023)
Phenalenone and several phenalenone derivatives have the remarkable capacity to produce singlet oxygen (1O2), via photosensitization, with singlet oxygen quantum yield values close to unity in most solvents. Considerable efforts have been made to obtain phenalenones that red-shifted their absorption but maintaining the high capacity of generation of singlet oxygen. The presence of electron donors on specific positions of the aromatic ring promotes important changes. Herein, with the presence of a dimethylamino substituent in position 3 or 6, we were able to modulate singlet oxygen generation capacity and fluorescence. Both, 3DMAPNF and 6DMAPNF show red-shifted absorption (compared with phenalenone) associated with ππ* transitions. Solvent effect in absorption and emission properties were observed for 6DMAPNF, while that for 3DMAPNF no fluorescence response was observed. Both, show a decrease in singlet oxygen quantum yield with polarity of solvent, always with 3DMAPNF singlet oxygen quantum yield values greater than for 6DMAPN. No singlet oxygen generation was observed for both compounds in H2O. © 2023 Elsevier B.V.